Neuropilin-1: A Conserved Entry Receptor for SARS-CoV-2 and a Potential Therapeutic Target - Vivany Maydel Sierra-Sánchez; Citlali Margarita Blancas-Napoles; Aina Daniela Sánchez-Maldonado; Indira Medina; Rodrigo Romero-Nava; Fengyang Huang; Enrique Hong; Asdrúbal Aguilera-Méndez; Sergio Adrian Ocampo-Ortega; Santiago Villafaña (Biomedicines, 2025)
Background/Objectives: Neuropilin-1 (NRP1) is a key co-receptor for SARS-CoV-2, complementing the ACE2 receptor. Several investigations have documented highly conserved sequences in this receptor, supporting the implication of NRP1 as a key mediator in SARS-CoV-2 cellular entry mechanisms. Methods: To investigate this hypothesis, we examined 104,737 SARS-CoV-2 genome fastas from GISAID genomic data, corresponding to isolates collected between 2020 and 2025 in Mexico. Specifically, we focused on the RRAR motif, a known furin-binding site for NRP-1 and the binding site for ACE2 with the spike protein. Our analysis revealed high conservation (>98%) of the RRAR domain compared to a rapidly diminishing ACE2-binding domain. A complementary analysis, using Data from Gene Expression Omnibus (GEO, GSE150316), showed that NRP1 expression in lung tissue remains relatively stable, whereas ACE2 displayed high inter-individual variability and lower abundance compared to NRP1. Based on this evidence, we designed two humans–rats NRP1 siRNAs that were tested in vivo using a melittin-induced lung injury model. Results: The RT-PCR assays confirmed an effective NRP1 knockdown, and the siRNA-treated group showed a significant reduction in the lesions severity. These findings highlight NRP1 as a stable and relevant therapeutic target and suggest the protective potential of siRNA-mediated gene silencing. Conclusions: The evidence presented here supports the rational design of NRP1-directed therapies for multiple circulating SARS-CoV-2 variants in Mexico.